Characterization of complex planar faults in FeAl(B) alloys. (April 2017) - Viguier, Bernard; Martinez, Mayerling; Lacaze, Jacques
Abstract: Complex planar faults were observed by diffraction contrast transmission electron microscopy in a B2 FeAl based alloy containing Ni and B. The comparison of experimental images to simulated ones revealed the detailed structure of these faults that lie on 001 planes with both in-plane and out-of-plane components of the displacement vector. It was deduced that these defects form by segregation of (B-Al vacancies) complexes on a<100> dislocations, leading to various defect structures depending on the screw or edge character of the dislocation. Graphical abstract: Highlights: Complex planar faults are observed in a B-containing FeAl alloy with B2 structure. These were characterized by a comparison of experimental and simulated TEM images. The out of plane component of the defect is quantified. The defects form by segregation of B ona [100] dislocation and dissociation on100 plane.